Campur Kode Pada Gelar Wicara Mata Najwa Episode â€œBelajar dari Buya Hamkaâ€ dan Implikasinya Terdahap Pembelajaran Bahasa - Niken Putri Azizah; Rafik M Abasa; Nasrullah La Madi; Suhardi Kasim (EDUKASI, 2024)
The formulation of the problems in this study are (1) How is the form of inward code mix and outward code mix in Gelar Wicara Mata Najwa Episode "Belajar dari Buya Hamka" (2) How is the implication of code mix in language learning. The research objectives to be achieved are to know the form of inward code mix and the form of outward code mix in Gelar Wicara Mata Najwa Episode "Belajar dari Buya Hamka" and to know the implications of code mix on language learning. The method used in this research is descriptive qualitative method. The data in this research is the dialog of moderators and speakers. The data source used in this research is Mata Najwa Talk Show Episode "Learning from Buya Hamka". Based on data analysis and conclusions, it is known that (1) The form of inward code mix in Gelar Wicara Mata Najwa Episode "Belajar dari Buya Hamka" is the use of two languages in one dialog, namely Indonesian and local languages. (2) The form of outward code mix in Gelar Wicara Mata Najwa Episode "Belajar dari Buya Hamka" is the use of two languages in one dialog, namely Indonesian and foreign languages. (3) Code mixing is implied in Indonesian language learning in the form of learning media produced, namely posters and slogans related to the results of code mixing in Gelar Wicara Mata Najwa Episode "Belajar dari Buya Hamka".Â Â